Sporadic Medullary Thyroid Carcinoma with Paraneoplastic Cushing Syndrome. (8th December 2019) - Pivovarova, Aleksandra I.; Patrick, Stephanie; Reddy, Punuru J.
Abstract : Medullary thyroid cancer (MTC) is a rare form of neoplasm affecting the thyroid gland. This neuroendocrine tumor is capable of releasing active substances causing systemic manifestation in the form of flushing, diarrhea, and uncommonly, Ectopic Cushing's syndrome (ECS). MTC can be hereditary as a part of multiple endocrine neoplasm type 2 syndrome (MEN2) or arise sporadically. We report a case of a 74-year-old female presenting with chronic diarrhea, in whom diagnosis of sporadic MTC was delayed due to previous history of gastrointestinal (GI) disturbances. The patient developed liver metastases yielding ACTH dependent Cushing's Syndrome leading to abnormal clinical presentation and laboratory values driven by elevated cortisol level. Metastatic MTC should be considered in patients presenting with chronic diarrhea and weakness unexplained by other GI related causes.